Implementation of Reputational Risk Management in Maintaining the Company’s Positive Image at Bank Syariah Indonesia - Nurfadillah, Viona Anggraini (Maliki Interdisciplinary Journal, 2025)
Banks have an important role in Indonesia’s economic development, but they are still faced with risks that can threaten operational sustainability, one of which is reputation risk. Reputation risk arises from declining public trust due to customer complaints, cyber attacks, and negative publicity. This research discusses the implementation of reputation risk management by BSI to maintain the company’s positive image. BSI applies preventive and responsive approaches through communication strategies, complaint resolution, and establishing a Communication Command Center. Risk measurement is done through the Publicity Effectiveness Level (PEL) and an integrated complaint system. This reputation risk management approach aims to minimize negative impacts on the bank’s reputation and maintain stakeholder trust. The results show that proactive and integrated reputation risk management is key to BSI’s success in maintaining its reputation and supporting long-term business sustainability.